3(2y-3)=5(y+4)

Simple and best practice solution for 3(2y-3)=5(y+4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2y-3)=5(y+4) equation:


Simplifying
3(2y + -3) = 5(y + 4)

Reorder the terms:
3(-3 + 2y) = 5(y + 4)
(-3 * 3 + 2y * 3) = 5(y + 4)
(-9 + 6y) = 5(y + 4)

Reorder the terms:
-9 + 6y = 5(4 + y)
-9 + 6y = (4 * 5 + y * 5)
-9 + 6y = (20 + 5y)

Solving
-9 + 6y = 20 + 5y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-5y' to each side of the equation.
-9 + 6y + -5y = 20 + 5y + -5y

Combine like terms: 6y + -5y = 1y
-9 + 1y = 20 + 5y + -5y

Combine like terms: 5y + -5y = 0
-9 + 1y = 20 + 0
-9 + 1y = 20

Add '9' to each side of the equation.
-9 + 9 + 1y = 20 + 9

Combine like terms: -9 + 9 = 0
0 + 1y = 20 + 9
1y = 20 + 9

Combine like terms: 20 + 9 = 29
1y = 29

Divide each side by '1'.
y = 29

Simplifying
y = 29

See similar equations:

| 30+8+7+10+25-4+9+25-3+6-5=108 | | x^2+2x-15=15 | | H+9.7=-9 | | x^3-2x^2-41x-56=0 | | 3xy+2x=4y | | 3(x+5)=6x+15 | | 4x+7=2x+9+7x-4 | | 4.1=d-5.1 | | 3.1x-1.6=5 | | 3=2x+1(x) | | (x)(x)+4x=117 | | 6(a+2b)+8b-16b= | | 5.6+z=3 | | 3x-2=130 | | 7-6y=31-4x | | 6x+6y=224.9 | | 5x+7+2x=4 | | 7x-8=4x-56 | | 2(8+p)= | | 4x+3x^2=7+5x | | X-7+3x-1=0 | | 6n=3n+42 | | -5x-31=7x+5 | | 6x+9=4x+39 | | -6+4x=5x+4 | | .023809523809529/1*1000/1000= | | n+10=n^2+16 | | .3(x+60)+.7x=43 | | 3x-0.01x^2=200 | | t^2-8t-10=0 | | a^2-111a-2160=0 | | -4a+8+6a=9a-5a |

Equations solver categories